Determinants of Dividend Policy - Ratna Wijayanti Daniar Paramita (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This study aims to analyze the influence of Free Cash Flow, Profitability, Liquidity and Leverage on Dividend Policy. This research was conducted at manufacturing companies listed on the Indonesian Stock Exchange in the Consumer Goods Industry sector in the 2015-2018 period. The data analysis technique used multiple linear regression analysis. This study used purposive sampling technique to obtain samples according to the specified criteria. The number of companies based on the criteria in the study were 13 companies. The results of this research are free cash flow, liquidity, and leverage have no significant effect on dividend policy, while profitability has a significant positive effect on dividend policy.